Paralytic shellfish toxins in phytoplankton and shellfish samples collected from the Bohai Sea, China. (15th February 2017) - Liu, Yang; Yu, Ren-Cheng; Kong, Fan-Zhou; Chen, Zhen-Fan; Dai, Li; Gao, Yan; Zhang, Qing-Chun; Wang, Yun-Feng; Yan, Tian; Zhou, Ming-Jiang
Abstract: Phytoplankton and shellfish samples collected periodically from 5 representative mariculture zones around the Bohai Sea, Laishan (LS), Laizhou (LZ), Hangu (HG), Qinhuangdao (QHD) and Huludao (HLD), were analysed for paralytic shellfish toxins (PSTs) using an high-performance liquid chromatography (HPLC) method. Toxins were detected in 13 out of 20 phytoplankton samples, and N -sulfocarbamoyl toxins (C1/2) were predominant components of PSTs in phytoplankton samples with relatively low toxin content. However, two phytoplankton samples with high PST content collected from QHD and LS had unique toxin profiles characterized by high-potency carbamoyl toxins (GTX1/4) and decarbamoyl toxins (dcGTX2/3 and dcSTX), respectively. PSTs were commonly found in shellfish samples, and toxin content ranged from 0 to 27.6 nmol/g. High level of PSTs were often found in scallops and clams. Shellfish from QHD in spring, and LZ and LS in autumn exhibited high risks of PST contamination. Highlights: Phytoplankton and shellfish samples were collected from 5 sites around Bohai Sea. Paralytic shellfish toxins (PSTs) in the samples were analysed using an HPLC method. PSTs were detected in 13 out of 20 net-concentrated phytoplankton samples. Toxic Alexandrium spp. and Gymnodinium catenatum were potential producers of PSTs. PSTs present in nearly all shellfish samples, scallops and clams had highest level of toxin.